COVID-19 pandemic impact on the pharmaceutical sector in Bulgaria - Veselina Ivanova; Deyan Pavlov; Tolya Assenova; Emily Terzieva; Petya Milushewa; Alime Djemadan; Gergana Vladimirova; Maria Dimitrova; Maria Kamusheva (Pensoft Publishers, 2021)
In December, 2019 in Wuhan, Hubei Province, China, a new, unknown strain of coronavirus called SARS-CoV-2 was identified. The virus has spread rapidly to other countries around the world, among which the most affected were Italy, Spain and the United States. As a result, in March 2020 The WHO has declared the new coronavirus epidemic a global pandemic. Despite timely measures and efforts to reduce morbidity, up to date, confirmed cases are 119,452,269, while the number of deaths reached 2,647,662 people. The COVID-19 pandemic has affected all areas of human life - health, social, economic. In each of them, a number of restrictions and obligations were imposed, including wearing of masks, use of disinfectants, education in an online environment, limited work in restaurants and shops. The health sector was particularly affected, and all actors in the pharmaceutical system had to reorganize and adapt their activities in the name of a common goal - ending the COVID-19 pandemic.